Forms of capital lectures at the Collège de France (1983-1984) - Bourdieu, Pierre 1930-2002 (Polity Press, 2021)
"One of the greatest sociologists of the 20th century introduces a key concept of his approach"--
Keywords: Soziologie; Klassifikation; Sociology / Study and teaching (Higher) / France; Capital; Capitalism; Sociology; Sociology / Study and teaching (Higher); France